Steroids and endocrine disruptors--History, recent state of art and open questions - Hampl, Richard; Kubátová, Jana; Stárka, Luboslav (The Journal of steroid biochemistry and molecular biology, 2016)
This introductory chapter provides an overview of the levels and sites at which endocrine disruptors (EDs) affect steroid actions. In contrast to the special issue of Journal of Steroid Biochemistry and Molecular Biology published three years ago and devoted to EDs as such, this paper focuses on steroids. We tried to point to more recent findings and opened questions. EDs interfere with steroid biosynthesis and metabolism either as inhibitors of relevant enzymes, or at the level of their expression. Particular attention was paid to enzymes metabolizing steroid hormones to biologically active products in target cells, such as aromatase, 5α-reductase and 3β-, 11β- and 17β-hydroxysteroid dehydrogenases. An important target for EDs is also steroid acute regulatory protein (StAR), responsible for steroid precursor trafficking to mitochondria. EDs influence receptor-mediated steroid actions at both genomic and non-genomic levels. The remarkable differences in response to various steroid-receptor ligands led to a more detailed investigation of events following steroid/disruptor binding to the receptors and to the mapping of the signaling cascades and nuclear factors involved. A virtual screening of a large array of EDs with steroid receptors, known as in silico methods (≡computer simulation), is another promising approach for studying quantitative structure activity relationships and docking. New data may be expected on the effect of EDs on steroid hormone binding to selective plasma transport proteins, namely transcortin and sex hormone-binding globulin. Little information is available so far on the effects of EDs on the major hypothalamo-pituitary-adrenal/gonadal axes, of which the kisspeptin/GPR54 system is of particular importance. Kisspeptins act as stimulators for hormone-induced gonadotropin secretion and their expression is regulated by sex steroids via a feed-back mechanism. Kisspeptin is now believed to be one of the key factors triggering puberty in mammals, and various EDs affect its expression and function. Finally, advances in analytics of EDs, especially those persisting in the environment, in various body fluids (plasma, urine, seminal fluid, and follicular fluid) are mentioned. Surprisingly, relatively scarce information is available on the simultaneous determination of EDs and steroids in the same biological material. This article is part of a Special Issue entitled 'Endocrine disruptors & steroids'.
Keywords: Overreview; signální transdukce; Signal Transduction; 17-hydroxysteroidní dehydrogenasy; Humans; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; regulace genové exprese; History, 21st Century; Endocrine Disruptors; rychlé screeningové testy; Molecular Docking Simulation; dějiny 20. století; History, 20th Century; dějiny 21. století; lidé; pohlavní steroidní hormony; systém hypotalamus-hypofýza; Endocrine disruptors; endokrinní disruptory; systém hypofýza - nadledviny; Receptors, Steroid; Gene Expression Regulation; Pituitary-Adrenal System; 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; steroidní receptory; globulin vázající pohlavní hormony; Gonadal Steroid Hormones; 3-oxo-5-alfa-steroid-4-dehydrogenasa; 17-Hydroxysteroid Dehydrogenases; Steroids; Hypothalamo-Hypophyseal System; High-Throughput Screening Assays; Transcortin; transkortin; Sites of action; Sex Hormone-Binding Globulin